Cathode material, cathode material preparation method and related sample preparation method
Through the preparation of the zinc-doped perovskite oxide cathode material Sr3Fe1.5Zn0.5O7-δ, the problems of insufficient electrocatalytic activity and CO2 tolerance of the existing Sr3Fe2O7-δ cathode material are solved, and higher stability and electrochemical performance in medium and low temperature SOFC are achieved.
Patent Information
- Application Number
- CN202411717715.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-28
AI Technical Summary
The existing Sr3Fe2O7-δ cathode materials have poor electrocatalytic activity and CO2 tolerance, which limits their application in medium and low temperature SOFC.
By mixing and grinding, calcining and grinding the raw materials of SrCO3, Fe2O3 and ZnO, the zinc-doped perovskite oxide cathode material Sr3Fe1.5Zn0.5O7-δ was prepared.
The stability and electrocatalytic activity of the cathode material in a CO2-containing atmosphere are significantly improved, and it has good chemical stability with the BZCY electrolyte, which reduces the thermal expansion coefficient and improves the conductivity and electrochemical properties.
Smart Images

Figure CN119542442A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of solid oxide fuel cells, and in particular to a cathode material, a cathode material preparation method and a related sample preparation method. Background Art
[0002] Solid oxide fuel cells (SOFCs) are a promising new generation energy technology that can directly convert fuel gas into electricity in an economical, efficient, pollution-free and emission-free manner. However, the operating temperature of over 800°C ensures high ionic conductivity and low polarization resistance, but also accelerates the aging of the entire battery unit, including the degradation of electrode materials, thermal mismatch between components, and thermal aging of packaging materials. Therefore, the development of intermediate temperature SOFCs (IT-SOFCs) operating between 550°C and 700°C has become a hot topic and development direction of current research. Proton conducting solid oxide fuel cells (PCFCs) meet this demand. They have the advantages of higher conductivity at lower temperatures, no fuel dilution, and higher theoretical efficiency.
[0003] Traditional solid oxide fuel cell cathodes are mostly electronic conductors or mixed ion-electronic conductors, and the oxygen reduction reaction (ORR) only occurs at the triple phase interface (TBP). The specific reaction sites limit the further improvement of electrochemical performance. On the one hand, in order to improve the catalytic activity, strategies such as in-situ dissolution, morphology reconstruction, and component composition have been adopted; on the other hand, many researchers have developed triple-conducting conductors (TIECs) with more electrochemically active ORR sites, mainly perovskite oxides, as PCFC cathode materials. Cobalt-based perovskite oxides show good catalytic performance, but usually have a high thermal expansion coefficient and are difficult to couple with IT-SOFC electrolyte materials BZCY (i.e., BaZr 0.1 Ce 0.7 Y 0.2 O 3-δ ) matches, and at the same time, Co-based cathode materials are 2 and H 2 O has extremely poor stability, such as single perovskite oxides (La 0.6 Sr 0.4 ) 0.95 Co 0.2 Fe 0.8 O 3-δ (LSCF), PrNi 0.5 Co 0.5 O 3-δ (PNC) and double perovskite oxide Pr 0.2 Sr 1.8 TiCoO 6-δ(P02STC). And the high cost of cobalt limits its practical application in IT-SOFC. Therefore, the development of cobalt-free cathode materials is crucial for the medium and low temperature of solid oxide fuel cells.
[0004] In order to increase Sr 3 Fe 2 O 7-δ (SFO) type cathode stability in high steam atmosphere, Huan et al. have doped Eu and Co at the A and B sites respectively. 0.6 Sr 0.4 Co 0.2 Fe 0.8 O 3-δ Compared with air electrode, doped SrEu 2 Fe 1.8 Co 0.2 O 7-δ It has high catalytic activity and good stability.
[0005] Cobalt-based perovskite cathode materials have high thermal expansion coefficients and are difficult to match with the electrolyte material BZCY. 2 and H 2 The poor stability in O and the high cost of cobalt have limited its practical application in IT-SOFC. SFO has attracted wide attention in the application of IT-SOFC cathode materials due to its good mixed conductivity and strong stability in air atmosphere and certain proton conductivity. Although SFO cathode materials have good electrochemical properties compared to Co-based perovskite oxides, they are difficult to be used in CO-containing environments. 2 The electrocatalytic activity of SFO is related to CO 2 Tolerance still needs to be improved. Summary of the invention
[0006] The main purpose of the present invention is to provide a cathode material, a cathode material preparation method and a related sample preparation method to solve the problem of Sr 3 Fe 2 O 7-δ Electrocatalytic activity of cathode materials and CO 2 Poorly tolerated technical issues.
[0007] In order to achieve the above-mentioned object, the first aspect of the present invention provides a method for preparing a cathode material, comprising: 3 , Fe 2 O 3, ZnO, etc., to obtain a first finely mixed raw material; the first finely mixed raw material is calcined to obtain a crude perovskite oxide product; the crude perovskite oxide product is ground to obtain the cathode material Sr 3 Fe 1.5 Zn 0.5 O 7-δ .
[0008] Further, comprising: the SrCO 3 , the Fe 2 O 3 , the stoichiometric ratio of ZnO is 3:0.75:0.5.
[0009] Further, the said will include SrCO 3 , Fe 2 O 3 , ZnO and other raw materials are mixed and ground, including: the raw materials are ball-milled in a first solvent to obtain a mixed liquid; and the mixed liquid is dried.
[0010] Furthermore, the first solvent includes anhydrous ethanol.
[0011] Furthermore, the calcining of the first finely mixed raw material comprises: calcining the first finely mixed raw material at 1000° C. in an air environment.
[0012] The second aspect of the present invention provides a cathode material, which is prepared by the cathode material preparation method, and the chemical formula of the cathode material is Sr 3 Fe 1.5 Zn 0.5 O 7-δ .
[0013] The third aspect of the present invention provides a test sample preparation method, comprising: using the cathode material preparation method to prepare Sr 3 Fe 1.5 Zn 0.5 O 7-δ ; The Sr 3 Fe 1.5 Zn 0.5 O 7-δ and BaZr 0.1 Ce 0.7 Y 0.2 O 3-δ The same mass is mixed and ground to obtain a second fine mixed raw material; the second fine mixed raw material is calcined to obtain a test sample for testing the compatibility of SFZ05-BZCY.
[0014] A fourth aspect of the present invention provides a test sample preparation method, comprising: using the cathode material preparation method to prepare Sr 3 Fe 1.5 Zn 0.5 O 7-δ ; The Sr 3 Fe 1.5 Zn 0.5 O 7-δ The first pressed sheet is subjected to pressing treatment and sintering treatment. The first pressed sheet is subjected to silver coating treatment, drying treatment and calcining treatment to obtain a test sample for testing the electrical conductivity of SFZ05.
[0015] A fifth aspect of the present invention provides a battery preparation method, comprising: using the cathode material preparation method to prepare Sr 3 Fe 1.5 Zn 0.5 O 7-δ After mixing terpineol and turpentine, the Sr 3 Fe 1.5 Zn 0.5 O 7-δ Add and mix to obtain electrode slurry; apply the electrode slurry on BaZr by screen printing 0.1 Ce 0.7 Y 0.2 O 3-δ The two sides of the electrolyte sheet are calcined to obtain a first half-cell; the electrode attachment areas on both sides of the first half-cell are silver-coated and calcined to obtain a SFZ05|BZCY|SFZ05 symmetric half-cell for testing electrochemical impedance.
[0016] The sixth aspect of the present invention provides a method for preparing a battery, comprising: 0.1 Ce 0.7 Y 0.2 O 3-δ and starch are mixed and ground to obtain an anode support powder; the anode support powder is pressed to obtain an anode green body; BaZr is sprinkled on the anode green body through a sieve 0.1 Ce 0.7 Y 0.2 O 3-δ Electrolyte powder is pressed to obtain a double-layer green body; the double-layer green body is calcined to obtain a double-layer structure of NiO-BZCY anode porous support substrate|BZCY dense electrolyte; pine alcohol and turpentine are mixed and stirred, and Sr prepared by the cathode material preparation method is added 3 Fe 1.5 Zn 0.5 O 7-δThe mixture is put in to obtain an electrode slurry; the electrode slurry is applied to one side of the electrolyte of the double-layer structure by screen printing, and a calcination treatment is performed to obtain a first battery cell; the electrode attachment parts on both sides of the first battery cell are silver-coated, and a calcination treatment is performed to obtain a NiO-BZCY|BZCY|SFZ05 full battery for testing electrochemical power density.
[0017] The cathode material preparation method of the present invention is applied by 3 , Fe 2 O 3 , ZnO, etc., to obtain a first finely mixed raw material, calcine the first finely mixed raw material to obtain a crude perovskite oxide product, grind the crude perovskite oxide product to obtain a cathode material Sr 3 Fe 1.5 Zn 0.5 O 7-δ Through mixed grinding, calcination and other processing processes, the purity and performance of the final cathode material are guaranteed to meet the requirements; by introducing the zinc element, a pure phase cathode material with good chemical stability with the BZCY electrolyte is obtained, which not only improves the electrocatalytic activity, but also enhances its stability in a CO2 atmosphere.
[0018] The cathode material of the present invention introduces zinc element to obtain a pure phase cathode material with good chemical stability with BZCY electrolyte, which not only improves the electrocatalytic activity but also enhances its stability in an atmosphere containing CO2.
[0019] In addition, the test sample preparation method and the battery preparation method of the present invention adopt the above-mentioned cathode material preparation method to prepare the cathode material, and have all the beneficial effects of the above-mentioned cathode material preparation method. At the same time, it is also conducive to the chemical stability test of SFC05 and BZCY at high temperature, the conductivity test of SFZ05, the electrochemical impedance spectroscopy test of SFZ05|BZCY|SFZ05 symmetric half-cell, and the electrochemical power density test of NiO-BZCY|BZCY|SFZ05 full battery, so as to comprehensively verify the performance of SFZ05 cathode material. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0021] Figure 1 The XRD patterns of the SFZ05 cathode material powder, the BZCY electrolyte powder, and the powder after SFZ05 and BZCY were mixed and calcined at 900° C. in an air atmosphere for 10 hours in the embodiments of the present invention are shown;
[0022] Figure 2 The scanning electron microscope image of the SFZ05 powder in the embodiment of the present invention after being treated in an air atmosphere at 1000° C. for 5 hours is shown;
[0023] Figure 3 The SFZ05 powder in the embodiment of the present invention and the SFO powder in the comparative embodiment are pressed into tablets and sintered, and the conductivity data graph is measured;
[0024] Figure 4 The polarization impedance spectra of the SFZ05|BZCY|SFZ05 symmetric half-cell at 650°C and 700°C in an air atmosphere in an embodiment of the present invention are shown;
[0025] Figure 5 The polarization impedance spectra of the SFO|BZCY|SFO symmetric half-cell in the comparative embodiment of the present invention at 650°C and 700°C in air atmosphere are shown;
[0026] Figure 6 The power density diagram corresponding to 600°C-750°C of the NiO-BZCY|BZCY|SFZ05 full battery in an air atmosphere in an embodiment of the present invention is shown;
[0027] Figure 7 The power density diagram corresponding to 600°C-750°C of the NiO-BZCY|BZCY|SFO full battery in the comparative embodiment of the present invention is shown;
[0028] Figure 8 The CO of SFZ05 powder in the present invention example and SFO powder in the comparative example are shown. 2 Adsorption curve diagram. DETAILED DESCRIPTION
[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all the embodiments. The following description of at least one exemplary embodiment is actually only illustrative and is by no means intended to limit the present invention and its application or use. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0030] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit the exemplary embodiments according to the present application. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprise" and / or "include" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.
[0031] The first aspect of the present invention provides a method for preparing a cathode material, comprising: 3 , Fe 2 O 3 , ZnO, etc., to obtain a first finely mixed raw material; the first finely mixed raw material is calcined to obtain a crude perovskite oxide product; the crude perovskite oxide product is ground to obtain the cathode material Sr 3 Fe 1.5 Zn 0.5 O 7-δ (SFZ05).
[0032] Ruddlesden-Popper (RP) perovskite (A n+1 B n O 3n+1 ) consists of two layers of rock salt and an n-layer perovskite stack in between, and its ion composition and oxygen content are highly flexible. Non-cobalt RP perovskite has attracted much attention due to its excellent electrochemical performance and long-term stability. The thermal expansion coefficient of perovskite cathode materials containing iron is lower, closer to the thermal expansion coefficient of BZCY, and has a higher thermal match with BZCY electrolyte. Among them, RP perovskite-type strontium iron oxide (Sr 3 Fe 2 O 7-δ The Fe element in SFO has variable spin states and oxidation states, which can improve the catalytic activity of cathode materials. At the same time, the Sr element in SFO has a lower chemical valence and a larger ionic radius, which can provide abundant oxygen vacancies. Iron-based perovskites also have advantages such as higher stability and lower production costs. These advantages make SFO a popular IT-SOFC cathode material today.
[0033] Wherein, the SrCO 3 , the Fe 2 O 3 , the stoichiometric ratio of ZnO is 3:0.75:0.5.
[0034] In the above-mentioned cathode material preparation method, the raw materials are mixed and ground, and the grinding time, grinding equipment, grinding materials, etc. can be designed according to the needs. In this embodiment, optionally, the raw materials are ball-milled in the first solvent to obtain a mixed solution, and the mixed solution is dried to obtain a dried first fine mixed raw material, wherein the first solvent includes anhydrous ethanol, which can play a lubricating and dispersing role in the ball milling process, reduce the phenomenon of powder adhesion and agglomeration, and improve the ball milling efficiency. In addition, in order to ensure the grinding effect of ball milling, the grinding time can usually be designed to be about 10 to 15 hours. The mixed solution after ball milling should be dried in a drying oven at a temperature of about 70 to 90°C, and after drying, it is preferably ground again for 1 to 3 hours to obtain a first fine mixed raw material with better grinding effect.
[0035] After obtaining the first finely mixed raw material, the first finely mixed raw material is calcined to obtain a crude perovskite oxide product. In this embodiment, the first finely mixed raw material is in an air environment, the calcination temperature can be designed to be about 1000° C. (preferably 1000° C.), and the calcination time is generally 4 to 6 hours, preferably 5 hours, thereby obtaining a crude perovskite oxide product. By controlling the calcination temperature and time, the microstructure and phase purity of the material are optimized.
[0036] The crude perovskite oxide product still needs to be ground, and the grinding time can be designed to be 1 to 3 hours to obtain a fine powder product, that is, the cathode material Sr 3 Fe 1.5 Zn 0.5 O 7-δ , that is, RP perovskite-type strontium iron oxide.
[0037] Combination Figure 1 As shown, the cathode material SFZ05 obtained in this embodiment is a single RP perovskite structure without any impurity phase. By comparing the three curves, it is shown that the SFZ05 cathode material and the BZCY electrolyte have good chemical stability at 900°C and below.
[0038] Combination Figure 2 As shown, after SFZ05 powder was calcined at 1000°C in air atmosphere for 5 hours, the particle size of the powder particles was uniform, ranging from 2 to 4 μm.
[0039] Zinc doping has a significant effect on the oxygen vacancy concentration of RP perovskite cathode materials. Since the valence of zinc ions is usually +2, their partial replacement of iron ions will reduce the average valence of the material, thereby promoting the formation of more oxygen vacancies. These oxygen vacancies, as channels for oxygen ion transmission, are essential for improving the ionic conductivity and catalytic activity of cathode materials. In addition, the larger ionic radius of zinc ions may cause lattice distortion, further increasing the concentration and mobility of oxygen vacancies, thereby improving the electrical conductivity and electrochemical performance of the material. Zinc doping also significantly affects the polarization impedance of SFZ05 cathode materials. Polarization impedance is an important parameter for measuring electrode reaction kinetics, which reflects the difficulty of the charge transfer process on the electrode surface. Under SOFC operating conditions, SFZ05 cathode materials exhibit low polarization impedance, which is mainly attributed to its abundant oxygen vacancies and good electronic conductivity. The introduction of zinc not only increases the concentration of oxygen vacancies, but also improves the electronic structure of the material and promotes the rapid transmission of electrons on the electrode surface. In addition, zinc ion doping may also change the microscopic morphology and pore structure of the electrode surface, increase the contact area between the electrode and the electrolyte, and further reduce the polarization impedance. At the same time, zinc doping may also improve the stability and corrosion resistance of the material, allowing it to maintain excellent performance during long-term operation.
[0040] The zinc-doped RP perovskite Sr 3 Fe 1.5 Zn 0.5 O 7-δ The cathode material of medium-temperature proton-conducting solid oxide fuel cells first has high-temperature stability with the electrolyte material and will not react with the electrolyte under battery operating conditions; compared with Fe, Zn with a larger radius successfully enters the perovskite unit cell, and the unit cell parameters become larger, with a lower conduction barrier; Zn with a relatively low valence 2+ , leading to further oxidation of Fe to maintain the electrical neutrality of the oxide, while the oxygen vacancy content is increased, enhancing the conductivity.
[0041] The Sr obtained by the present invention 3 Fe 1.5 Zn 0.5 O 7-δ Compared with undoped materials, it has higher conductivity, lower polarization impedance, more efficient fuel gas utilization, and higher CO 2 Stability, with good application prospects. According to the test, the zinc-doped RP perovskite medium-temperature proton-conducting solid oxide fuel cell cathode material of the present invention has good catalytic activity for oxygen reduction reaction and excellent electrochemical performance at medium temperature between 600-750°C, and can simultaneously meet the performance requirements and operating condition requirements of medium-temperature SOFC cathode, and can be used as medium-temperature SOFC cathode material.
[0042] The cathode material preparation method provided in the first aspect of the present invention comprises: 3 , Fe 2 O 3 , ZnO, etc., to obtain a first finely mixed raw material, calcine the first finely mixed raw material to obtain a crude perovskite oxide product, grind the crude perovskite oxide product to obtain a cathode material Sr 3 Fe 1.5 Zn 0.5 O 7-δ The purity and performance of the cathode material finally obtained are ensured to meet the requirements through mixed grinding, calcination and other processing processes; Sr 3 Fe 1.5 Zn 0.5 O 7-δ The introduction of zinc element not only reduces the thermal expansion coefficient of the cathode material, improves the electrocatalytic activity and the matching degree between the cathode material and the BZCY electrolyte, but also enhances its performance in the presence of CO 2 Stability in atmosphere; by controlling the amount of zinc doping, the microstructure and phase purity of the cathode material are optimized, which not only ensures its excellent electrochemical properties, but also improves the practicality and durability of the cathode material.
[0043] The second aspect of the present invention provides a cathode material, such as Figure 2 As shown, the cathode material is prepared by the above preparation method, and the chemical formula of the cathode material is Sr 3 Fe 1.5 Zn 0.5 O 7-δ .
[0044] The cathode material Sr proposed in the second aspect of the present invention 3 Fe 1.5 Zn 0.5 O 7-δ , which introduced the zinc element to obtain a pure phase cathode material with good chemical stability with the BZCY electrolyte, which not only improved the electrocatalytic activity but also enhanced its stability in a CO2 atmosphere.
[0045] The third aspect of the present invention provides a test sample preparation method, comprising: using the above cathode material preparation method to prepare Sr 3 Fe 1.5 Zn 0.5 O 7-δ ; The Sr 3 Fe 1.5 Zn 0.5 O 7-δ and BaZr 0.1 Ce 0.7 Y0.2 O 3-δ The same mass is mixed and ground to obtain a second fine mixed raw material; the second fine mixed raw material is calcined to obtain a test sample for testing the compatibility of SFZ05-BZCY.
[0046] In the above test sample preparation method, the Sr 3 Fe 1.5 Zn 0.5 O 7-δ and BaZr 0.1 Ce 0.7 Y 0.2 O 3-δ The same mass is mixed and ground to obtain a second fine mixed raw material. In this embodiment, ball milling is preferably used for grinding. 3 Fe 1.5 Zn 0.5 O 7-δ and BaZr 0.1 Ce 0.7 Y 0.2 O 3-δ If equal mass is put into a ball mill, ball milling balls and a second solvent (the second solvent includes anhydrous ethanol, etc.) are added and ball milling is carried out for 1 to 3 hours (preferably 2 hours). After ball milling, the mixed solution is dried in a drying oven at 70 to 90° C. for 4 to 6 hours (preferably dried at 80° C. for 5 hours). After drying, it can be further ground for 1 to 3 hours (preferably 2 hours) to obtain a second fine mixed raw material.
[0047] Further, the second fine mixed raw material is calcined to obtain a test sample for testing the compatibility of SFZ05-BZCY. In this embodiment, the second fine mixed raw material is calcined at a temperature of about 900°C (preferably 900°C) in an air environment for 9 to 11 hours (preferably 10 hours) to obtain a test sample (i.e., SFZ05-BZCY mixed powder), which can be used to test the chemical stability of SFZ05 cathode material and BZCY electrolyte at high temperature.
[0048] The third aspect of the present invention provides a test sample preparation method, wherein the test sample comprises SrCO 3 , Fe 2 O 3 , ZnO, etc., to obtain a first finely mixed raw material, calcine the first finely mixed raw material to obtain a crude perovskite oxide product, grind the crude perovskite oxide product to obtain a cathode material Sr 3 Fe 1.5 Zn 0.5 O 7-δThe purity and performance of the cathode material finally obtained are ensured to meet the requirements through mixed grinding, calcination and other processing processes; Sr 3 Fe 1.5 Zn 0.5 O 7-δ , which introduces zinc element to obtain a pure phase cathode material with good chemical stability with BZCY electrolyte, which not only improves the electrocatalytic activity, but also enhances its stability in a CO2 atmosphere, while ensuring its excellent electrochemical performance, but also improves the practicability and durability of the cathode material; through the cathode material Sr 3 Fe 1.5 Zn 0.5 O 7-δ The prepared SFZ05-BZCY mixed powder is used as a test sample to facilitate the chemical stability test of SFZ05 cathode material and BZCY electrolyte at high temperature, which is beneficial to evaluate the performance of SFZ05 cathode material.
[0049] A fourth aspect of the present invention provides a test sample preparation method, comprising: using the cathode material preparation method to prepare Sr 3 Fe 1.5 Zn 0.5 O 7-δ ; The Sr 3 Fe 1.5 Zn 0.5 O 7-δ The first pressed sheet is subjected to pressing treatment and sintering treatment. The first pressed sheet is subjected to silver coating treatment, drying treatment and calcining treatment to obtain a test sample for testing the electrical conductivity of SFZ05.
[0050] In the above test sample preparation method, the Sr prepared by the cathode material preparation method described above is 3 Fe 1.5 Zn 0.5 O 7-δ In this embodiment, the SFZ05 powder is pressed into a disc with a thickness of about 0.06 cm and a diameter of about 1.5 cm, and sintered at a temperature of about 1200° C. (preferably 1200° C.) in an air environment to obtain a more compact first tablet.
[0051] The first pressing sheet is subjected to silver coating, drying and calcination to obtain a test sample for testing the conductivity of SFZ05. In this embodiment, four silver wires are equidistantly bonded to the first pressing sheet with silver paste. To make the silver wires firm, the first pressing sheet after silver coating is dried at a temperature of about 150°C (preferably 150°C) for 0.5 to 1.5h (preferably 1h), and calcined at a temperature of about 600°C (preferably 600°C) in an air atmosphere for 0.5 to 1.5h (preferably 1h) to obtain a test sample.
[0052] The fourth aspect of the present invention provides a test sample preparation method, wherein the test sample comprises SrCO 3 , Fe 2 O 3 , ZnO, etc., to obtain a first finely mixed raw material, calcine the first finely mixed raw material to obtain a crude perovskite oxide product, grind the crude perovskite oxide product to obtain a cathode material Sr 3 Fe 1.5 Zn 0.5 O 7-δ The purity and performance of the cathode material finally obtained are ensured to meet the requirements through mixed grinding, calcination and other processing processes; Sr 3 Fe 1.5 Zn 0.5 O 7-δ The introduction of zinc element not only reduces the thermal expansion coefficient of the cathode material, improves the electrocatalytic activity and the matching degree between the cathode material and the BZCY electrolyte, but also enhances its performance in the presence of CO 2 atmosphere; by controlling the amount of zinc doping, the microstructure and phase purity of the cathode material are optimized, while ensuring its excellent electrochemical performance, the practicality and durability of the cathode material are also improved; by 3 Fe 1.5 Zn 0.5 O 7-δ The prepared silver-coated pressed sheets are used as test samples to facilitate the conductivity test of electrode materials and to help evaluate the performance of SFZ05 cathode materials.
[0053] A fifth aspect of the present invention provides a battery preparation method, comprising: using the cathode material preparation method to prepare Sr 3 Fe 1.5 Zn 0.5 O 7-δ After mixing terpineol and turpentine, the Sr 3 Fe 1.5 Zn 0.5 O 7-δAdd and mix to obtain electrode slurry; apply the electrode slurry on BaZr by screen printing 0.1 Ce 0.7 Y 0.2 O 3-δ The two sides of the electrolyte sheet are calcined to obtain a first half-cell; the electrode attachment areas on both sides of the first half-cell are silver-coated and calcined to obtain a SFZ05|BZCY|SFZ05 symmetric half-cell for testing electrochemical impedance.
[0054] In the above-mentioned battery preparation method, after terpineol and turpentine oil are mixed and stirred, the Sr 3 Fe 1.5 Zn 0.5 O 7-δ In this embodiment, terpineol and turpentine are mixed and stirred at a mass ratio of 5:95 to obtain an organic solvent, and the prepared SFZ05 powder is then added and mixed to obtain an electrode slurry.
[0055] Further, the electrode slurry is applied to the BaZr 0.1 Ce 0.7 Y 0.2 O 3-δ In this embodiment, the electrode slurry is symmetrically applied to the center of both sides of the BZCY electrolyte sheet by screen printing, and calcined at a temperature of about 950° C. (preferably 950° C.) in an air atmosphere for 4 to 6 hours (preferably 5 hours) to obtain the first half cell.
[0056] Furthermore, the electrode attachments on both sides of the first half-cell are silver-coated and calcined to obtain a SFZ05|BZCY|SFZ05 symmetrical half-cell for testing electrochemical impedance. Silver paste is applied to the electrode attachments on both sides of the first half-cell and led out with silver wires, and then calcined at about 600° C. (preferably 600° C.) in an air atmosphere for 0.5 to 1.5 h (preferably 1 h) to obtain a SFZ05|BZCY|SFZ05 symmetrical half-cell, which can be used for electrochemical impedance spectroscopy testing.
[0057] A fifth aspect of the present invention provides a method for preparing a battery, comprising: 3 , Fe 2 O 3 , ZnO, etc., to obtain a first finely mixed raw material, calcine the first finely mixed raw material to obtain a crude perovskite oxide product, grind the crude perovskite oxide product to obtain a cathode material Sr 3 Fe 1.5 Zn 0.5 O7-δ The purity and performance of the cathode material finally obtained are ensured to meet the requirements through mixed grinding, calcination and other processing processes; Sr 3 Fe 1.5 Zn 0.5 O 7-δ , which introduces zinc element to obtain a pure phase cathode material with good chemical stability with BZCY electrolyte, which not only improves the electrocatalytic activity, but also enhances its stability in a CO2 atmosphere, while ensuring its excellent electrochemical performance, but also improves the practicability and durability of the cathode material; through the cathode material Sr 3 Fe 1.5 Zn 0.5 O 7-δ The prepared SFZ05|BZCY|SFZ05 symmetrical half-cell is convenient for electrochemical impedance spectroscopy testing, which is beneficial for evaluating the performance of SFZ05 cathode material in battery applications.
[0058] The sixth aspect of the present invention provides a method for preparing a battery, comprising: 0.1 Ce 0.7 Y 0.2 O 3-δ and starch are mixed and ground to obtain an anode support powder; the anode support powder is pressed to obtain an anode green body; BaZr is sprinkled on the anode green body through a sieve 0.1 Ce 0.7 Y 0.2 O 3-δ Electrolyte powder is prepared and pressed to obtain a double-layer green body; the double-layer green body is calcined to obtain a double-layer structure of NiO-BZCY anode porous support substrate|BZCY dense electrolyte; pine alcohol and turpentine are mixed and stirred, and Sr prepared by the cathode material preparation method according to any one of claims 1 to 5 is added 3 Fe 1.5 Zn 0.5 O 7-δ The mixture is put in to obtain an electrode slurry; the electrode slurry is applied to one side of the electrolyte of the double-layer structure by screen printing, and a calcination treatment is performed to obtain a first battery cell; the electrode attachment parts on both sides of the first battery cell are silver-coated, and a calcination treatment is performed to obtain a NiO-BZCY|BZCY|SFZ05 full battery for testing electrochemical power density.
[0059] In the above-mentioned battery preparation method, NiO, BaZr 0.1 Ce 0.7 Y 0.2 O 3-δ, starch, and mixed and ground to obtain anode support powder. 0.1 Ce 0.7 Y 0.2 O 3-δ The mass ratio of starch is 6:4:1, and the mixture is put into a ball mill, and a third solvent (the third solvent includes anhydrous ethanol, etc.) and ball milling balls are added for ball milling. The ball milling time is 11 to 13 hours (preferably 12 hours), and then the mixed solution is put into a drying oven and dried at 70 to 90° C. (preferably 80° C.) for 4 to 6 hours to obtain an anode support powder.
[0060] Further, the anode support powder is pressed to obtain an anode green body. In this embodiment, a mold with a diameter of 15 mm is used for tableting, and about 0.4 g of the anode support powder is put into the mold, and the tablet press is dry pressed at a pressure of 150 MPa to obtain an anode green body.
[0061] Further, BaZr is sprinkled on the anode green body through a screen. 0.1 Ce 0.7 Y 0.2 O 3-δ In this embodiment, 0.08 g of BZCY electrolyte powder is evenly sieved and sprinkled on the anode green body using a sieve, and dry pressed at 220 MPa to obtain a double-layer green body with a thin layer of electrolyte covering the anode support.
[0062] Further, the double-layer green body is calcined to obtain a double-layer structure of NiO-BZCY anode porous support substrate | BZCY dense electrolyte. In this embodiment, the double-layer green body is calcined at about 1400° C. (preferably 1400° C.) for 5 to 7 hours (preferably 6 hours) to obtain a double-layer structure of NiO-BZCY anode porous support substrate | BZCY dense electrolyte.
[0063] Further, after mixing terpineol and turpentine, Sr 3 Fe 1.5 Zn 0.5 O 7-δ In this embodiment, pine alcohol and turpentine oil are mixed in a mass ratio of 5:95 and stirred to obtain an organic solvent, and the Sr obtained by the above cathode material preparation method is added. 3 Fe 1.5 Zn 0.5 O 7-δ The mixture is put into an organic solvent and mixed to obtain an electrode slurry.
[0064] Furthermore, the electrode slurry is applied to the electrolyte side of the double-layer structure by screen printing, and calcined to obtain a first cell. In this embodiment, the electrode slurry is symmetrically applied to the center of the electrolyte side of the double-layer structure by screen printing, and calcined in an air atmosphere at about 950° C. (preferably 950° C.) for 4 to 6 hours (preferably 5 hours) to obtain the first cell.
[0065] Furthermore, the electrode attachment locations on both sides of the first cell are silver-coated and calcined to obtain a NiO-BZCY|BZCY|SFZ05 full battery for testing electrochemical power density. In this embodiment, silver paste is applied to the electrode attachment locations on both sides of the first cell and led out with silver wires, and then calcined at about 600° C. (preferably 600° C.) in an air atmosphere for 0.5 to 1.5 h (preferably 1 h) to obtain a NiO-BZCY|BZCY|SFZ05 full battery.
[0066] A sixth aspect of the present invention provides a method for preparing a battery, comprising: 3 , Fe 2 O 3 , ZnO, etc., to obtain a first finely mixed raw material, calcine the first finely mixed raw material to obtain a crude perovskite oxide product, grind the crude perovskite oxide product to obtain a cathode material Sr 3 Fe 1.5 Zn 0.5 O 7-δ The purity and performance of the cathode material finally obtained are ensured to meet the requirements through mixed grinding, calcination and other processing processes; Sr 3 Fe 1.5 Zn 0.5 O 7-δ , which introduces zinc element to obtain a pure phase cathode material with good chemical stability with BZCY electrolyte, which not only improves the electrocatalytic activity, but also enhances its stability in a CO2 atmosphere, while ensuring its excellent electrochemical performance, but also improves the practicability and durability of the cathode material; through the cathode material Sr 3 Fe 1.5 Zn 0.5 O 7-δ The prepared NiO-BZCY|BZCY|SFZ05 full battery is convenient for electrochemical power density testing, which is beneficial for evaluating the performance of SFZ05 cathode material in batteries.
[0067] The present invention also provides comparative examples, including:
[0068] (1) Preparation of RP perovskite-type strontium iron oxide
[0069] According to RP perovskite medium-temperature proton-conducting solid oxide fuel cell cathode material Sr 3 Fe 2 O 7-δ The stoichiometric ratio of SrCO is 3:2. 3 and Fe 2 O 3 The oxide raw material is weighed and placed in a clean ball mill, and ball milling balls are added and anhydrous ethanol is added until the powder is completely submerged and fixed, and then the ball milling is performed for 12 hours; the ball milled mixture is dried in an oven at 80°C for 5 hours, and after drying, the powder is taken out and ground for 2 hours to obtain a fine mixed raw material; the fine powder is calcined at 1000°C in an air environment for 5 hours to obtain a crude perovskite oxide product; it is ground again for 2 hours to obtain RP perovskite-type Sr 3 Fe 2 O 7-δ (SFO) fine powder. Combined Figure 8 The results show that doping with zinc is important for cathode materials in CO 2 The stability under the atmosphere is improved.
[0070] (2) Preparation of electrode material conductivity test samples
[0071] The SFO powder was pressed into a disc with a thickness of about 0.06 cm and a diameter of 1.5 cm, and then calcined at 1200°C in air atmosphere for 2 hours to make it sintered and dense. After that, four silver wires were evenly bonded on the sintered dense disc with silver paste. In order to make the silver wire firm, the cathode material disc coated with silver was dried at 150°C for 1 hour, and then calcined at 600°C in air atmosphere for 1 hour to obtain the conductivity test sample of the electrode material. Figure 3 As shown, after zinc doping, the electrical conductivity of the material is greatly improved, which is beneficial to the reaction rate. The increase in electrical conductivity in a humid air atmosphere represents the proton conduction of the material.
[0072] (3) Preparation of symmetric half-cell for electrochemical impedance spectroscopy
[0073] The organic solvent was obtained by mixing pine alcohol and turpentine in a mass ratio of 5:95 and stirring evenly, and then the SFO powder was mixed with it to obtain the electrode slurry. The electrode slurry was symmetrically applied to the center of both sides of the BZCY electrolyte sheet by screen printing, and calcined at 950℃ in air atmosphere for 5h. Then, silver paste was applied to the electrode attachments on both sides of the electrolyte sheet and led out with silver wire, and then calcined at 600℃ in air atmosphere for 1h to obtain the SFO|BZCY|SFO symmetric half-cell for testing, which was used for electrochemical impedance spectroscopy test. Figures 4 to 5As shown, zinc doping improves the electrochemical performance of the cathode material in the symmetric half-cell, indicating that SFZ05 has excellent electrochemical oxygen reduction catalytic activity under air atmosphere conditions and can be used as a cathode material with excellent performance.
[0074] (4) Preparation of full battery for power density testing
[0075] NiO powder, BZCY electrolyte powder and starch were placed in a ball mill at a mass ratio of 6:4:1, and after adding anhydrous ethanol, the mixture was ball milled for 12 hours, and then dried in an oven at 80°C for 5 hours to obtain an anode support powder; 0.40 g of the anode support powder was placed in a mold with a diameter of 15 mm, and dry-pressed at a pressure of 150 MPa on a tablet press to form an initial pressing, and then the pressing rod was slowly rotated out, and 0.08 g of the initial pressing anode green body was evenly sieved on the screen. BZCY electrolyte powder is then dry-pressed at 220MPa to obtain a double-layer green body with a thin layer of electrolyte covering the anode support, and calcined at 1400℃ for 6h to obtain a double-layer structure of NiO-BZCY anode porous support substrate|BZCY dense electrolyte; pine alcohol and turpentine are mixed in a mass ratio of 5:95 and stirred evenly to obtain an organic solvent, and then SFO powder is mixed with it to obtain an electrode slurry, and the electrode slurry is symmetrically applied to the center of one side of the electrolyte by screen printing, calcined at 950℃ in air atmosphere for 5h, and then silver paste is applied to the electrode attachments on both sides of the battery cell and led out with silver wire, and calcined at 600℃ in air atmosphere for 1h to obtain a test NiO-BZCY|BZCY|SFO full battery for electrochemical power density testing. Combined with Figure 6 and Figure 7 As shown, zinc doping improves the electrochemical performance of the cathode material in the full battery, indicating that SFZ05 has excellent electrochemical oxygen reduction catalytic activity under air atmosphere conditions and can be used as a cathode material with excellent performance.
[0076] It should be noted that the use of words such as "first" and "second" to limit corresponding objects is only for the convenience of distinguishing the corresponding objects. Unless otherwise stated, the above words have no special meaning and therefore cannot be understood as limiting the scope of protection of the present invention.
[0077] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a cathode material, characterized in that: include: Mixing and grinding raw materials including SrCO3, Fe2O3, and ZnO to obtain a first finely mixed raw material; calcining the first finely mixed raw material to obtain a crude perovskite oxide product; The crude perovskite oxide product is ground to obtain the cathode material Sr3Fe 1.5 Zn 0.5 O 7-δ .
2. The preparation method according to claim 1, characterized in that: include: The stoichiometric ratio of the SrCO3, the Fe2O3 and the ZnO is 3:0.75:0.
5.
3. The preparation method according to claim 1, characterized in that: The mixed grinding process of the raw materials including SrCO3, Fe2O3 and ZnO comprises: ball-milling the raw materials in a first solvent to obtain a mixed solution; The mixed solution is dried.
4. The preparation method according to claim 3, characterized in that: The first solvent includes anhydrous ethanol.
5. The preparation method according to claim 1, characterized in that: The step of calcining the first finely mixed raw material comprises: The first finely mixed raw material is calcined at 1000° C. in an air environment.
6. A cathode material, characterized in that: The cathode material is prepared by the cathode material preparation method according to any one of claims 1 to 5, and the chemical formula of the cathode material is Sr3Fe 1.5 Zn 0.5 O 7-δ .
7. A method for preparing a test sample, characterized in that: include: Sr3Fe 1.5 Zn 0.5 O 7-δ ; The Sr3Fe 1.5 Zn 0.5 O 7-δ and BaZr 0.1 Ce 0.7 Y 0.2 O 3-δ Mix and grind the mixture of equal masses to obtain a second finely mixed raw material; The second finely mixed raw material is calcined to obtain a test sample for testing the compatibility of SFZ05-BZCY.
8. A method for preparing a test sample, characterized in that: include: Sr3Fe 1.5 Zn 0.5 O 7-δ ; The Sr3Fe 1.5 Zn 0.5 O 7-δ Performing a pressing process and a sintering process to obtain a first pressed tablet; The first pressed sheet is subjected to silver coating, drying and calcining to obtain a test sample for testing the electrical conductivity of SFZ05.
9. A method for preparing a battery, characterized in that: include: Sr3Fe 1.5 Zn 0.5 O 7-δ ; After terpineol and turpentine oil are mixed and stirred, the Sr3Fe 1.5 Zn 0.5 O 7-δ Add and mix to obtain electrode slurry; The electrode paste is applied on the BaZr 0.1 Ce 0.7 Y 0.2 O 3-δ The electrolyte sheet is placed on both sides and calcined to obtain a first half cell; The electrode attachment areas on both sides of the first half-cell were silver-coated and calcined to obtain the SFZ05|BZCY|SFZ05 symmetric half-cell for testing electrochemical impedance.
10. A method for preparing a battery, characterized in that: include: NiO, BaZr 0.1 Ce 0.7 Y 0.2 O 3-δ , starch, and mixed and ground to obtain anode support powder; Pressing the anode support powder to obtain an anode green body; BaZr is sprinkled on the anode green body through a screen. 0.1 Ce 0.7 Y 0.2 O 3-δ Electrolyte powder is pressed to obtain a double-layer green body; The double-layer green body is calcined to obtain a double-layer structure of NiO-BZCY anode porous support substrate|BZCY dense electrolyte; After terpineol and turpentine are mixed and stirred, Sr3Fe 1.5 Zn 0.5 O 7-δ Add and mix to obtain electrode slurry; Applying the electrode slurry to one side of the electrolyte of the double-layer structure by screen printing, and performing calcination to obtain a first battery cell; The electrode attachment areas on both sides of the first battery cell were silver-coated and calcined to obtain a NiO-BZCY|BZCY|SFZ05 full battery for testing electrochemical power density.